Wearable Devices: Ultrathin, Washable, and Large‐Area Graphene Papers for Personal Thermal Management (Small 44/2017). Issue 44 (22nd November 2017) - Guo, Yang; Dun, Chaochao; Xu, Junwei; Mu, Jiuke; Li, Peiyun; Gu, Liwen; Hou, Chengyi; Hewitt, Corey A.; Zhang, Qinghong; Li, Yaogang; Carroll, David L.; Wang, Hongzhi
Abstract : In article number1702645, by Yaogang Li, David L. Carroll, Hongzhi Wang, and co‐workers, a scaled‐up blade‐coating method for preparing ultrathin, freestanding, and washable graphene papers with excellent electrical and thermal properties is reported. The graphene papers are integrated into textiles, and used as a bifuctional personal thermal management device for cooling or warming under various ambient conditions.